Commercial real estate analysis and investments - Geltner , David M.; Miller, Norman G.; Clayton, Jim; Eichholtz, Piet (Cengage Learning, 2007)
Presenting the essential concepts, principles, and tools for the analysis of commercial real estate, this real estate text provides you with the tools you need to understand real estate investments in today's dynamic economy.